Electrocardiographic effects of four antimalarials for pregnant women with uncomplicated malaria on the Thailand-Myanmar border: A randomised controlled trial - Saito, M; Yotyingaphiram, W; Cargill, Z; Gilder, ME; Min, AM; Phyo, AP; San, TD; Poe, H; Chu, C; White, NJ; Nosten, F; McGready, R (American Society for Microbiology, 2021)
Quinoline antimalarials cause drug-induced electrocardiograph QT prolongation, a potential risk factor for torsade de pointes. The effects of currently used antimalarials on the electrocardiogram were assessed in pregnant women with malaria. Pregnant women with microscopy-confirmed parasitaemia of any malaria species were enrolled in an open-label randomised controlled trial on the Thailand-Myanmar border in 2010–2016. Patients were randomised to the standard regimen dihydroartemisinin-piperaquine (DP), artesunate-mefloquine (ASMQ), or an extended regimen of artemether-lumefantrine (AL+). Recurrent vivax infections were treated with chloroquine. Standard 12-lead electrocardiograms were assessed on day 0, 4-6 hour following the last dose and day 7. QT was corrected for the heart rate by a linear mixed-effects model derived population-based correction formula (QTcP = QT/RR0.381). A total of 86 AL+, 82 ASMQ, 88 DP and 21 chloroquine treated episodes were included. No patients had an uncorrected QT interval nor QTcP > 480ms at any time. QTcP corresponding to peak drug concentration was longer in DP group (adjusted predicted mean difference 17.84 ms, 95% CI 11.58 to 24.10, p<0.001) and chloroquine group (18.31 ms, 95% CI 8.78 to 27.84, p<0.001) than in the AL+ group, but not different in the ASMQ group (2.45 ms, 95% CI -4.20 to 9.10, p=0.47). There was no difference between DP and chloroquine (p=0.91). QTc prolongation resulted mainly from widening of JT interval. In pregnant women, none of the antimalarial drug treatments exceeded conventional thresholds for an increased risk of torsade de pointes.